2001
DOI: 10.1001/archotol.127.9.1089
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Squamous Cell Carcinoma in Elderly Patients

Abstract: Head and neck squamous cell carcinoma in elderly patients did not seem to have a significantly different outcome when compared with head and neck squamous cell carcinoma occurring in younger patients. When properly monitored, conventional therapies seem feasible in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 12 publications
4
93
2
2
Order By: Relevance
“…In contrast to some reports [9][10][11], it was our observation, as well as that of others [12,13] that the older patients in general had less advanced disease. This distribution of stage in favour of the older patients was accentuated after exclusion of the early stage glottic carcinomas.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to some reports [9][10][11], it was our observation, as well as that of others [12,13] that the older patients in general had less advanced disease. This distribution of stage in favour of the older patients was accentuated after exclusion of the early stage glottic carcinomas.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the group of patients older than 65 had the poorest survival rate, the fact that 40% of the patients older than 65 were alive and free of disease at the closure of this study, strongly suggests that treatment is worthwhile in patients at an advanced age, regarding the disease-free survival for SCCHN. This observation concurs with observations in materials similar to the present study [1,13]. Other reports further substantiate the opinion that age in itself is not an independent prognostic factor, neither is it in itself a decisive factor for survival of SCCHN [9,11,[15][16][17].…”
Section: Discussionsupporting
confidence: 93%
“…No entanto, apesar de vários autores optarem por valores mais amplos, foi utilizado o critério da Organização Mundial da Saúde (OMS), que indica a idade de 60 anos como início da terceira idade nos países em desenvolvimento (42) . Ao contrário de outro estudo (37) , foi encontrado um comportamento diferente entre os grupos de idade, mostrando diferenças significativas nas curvas de sobrevivência, sugerindo que a diminuição da sobrevida nos mais idosos pode ocorrer devido à maior incidência de doenças debilitantes, maiores seqüelas pós-tratamento e complicações associadas ao envelhecimento.…”
Section: Discussionunclassified
“…It was also stressed that elderly patients cannot be excluded from chemoradiotherapy programs of organ preservation and patients aged 70 Á79 without severe comorbidities must be treated in the same exact manner as younger patients, but supportive treatment must be increased. In a retrospective review of 273 cases on head and neck cancers in elderly patients it was concluded that when properly monitored, conventional therapies seem feasible in older patients [17]. Same results have been achieved from studies on treatment of gastrointestinal cancers.…”
Section: Discussionmentioning
confidence: 99%